PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN ASESMEN PORTOFOLIO TERHADAP PRESTASI BELAJAR IPA DENGAN KOVARIABEL GAYA BELAJAR PADA SISWA KELAS IV A SD NEGERI 4 KAMPUNG BARU - Komang Trisna Mahartini (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
This study aims to determine (1) differences in students ' science learning achievementafter learning by using a scientific approach aided the portfolio assessment, (2) differences instudents' science learning achievement after learning by using a scientific approach aidedassessment portfolio, after controling the learning variable styles, and (3) contribution ofcovariates learning style on science learning achievement in IV grade of SD Negeri 4 KampungBaru. The type of this study is pre-experimental study with research design with one grouppretest posttest design. The study population was all students in IV grade on A class of SD N 4Banjar Tegal at 2014/2015 academic year and consisting of 28 students. This research sample isIV grade on A class of SD Negeri 4 Kampung Baru and the totaling 28 students selected to studycensus techniques. Data collection instruments used in this study is the science achievement testand test Learning Styles. Data were analyzed using descriptive and inferential statistics. Basedon the results of the data analysis, the results are as follows. First there are significant differencesof science student learning achievement after learning by using scientific approach assistedassessment portfolio (Fhitung = 62.642> Ftabel = 4.22), second, there is a significant differenceon students' science learning achievement after learning by using a scientific approach aidedthe portfolio assessment after learning styles are controlled the variable (F count = 45.526>Ftabel = 4.22), and third, there are a significant contribution on covariates learning stylestoward students' science learning achievement (Fhitung = 0.505> Ftabel = 0.374).Keywords: Learning Achievement, Scientific Approach, Learning Style